Pengaruh Multimedia Interaktif terhadap Hasil Belajar Siswa pada Materi Sistem Pencernaan - Elvia Siska; Diva Anggraini; Saskia Maharani (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2026)
The digestive system is one of the most abstract and complex topics in high school biology because it involves physiological processes that occur inside the body and cannot be observed directly. This situation calls for the use of instructional media that can help students understand concepts in a more concrete, systematic, and engaging way. This study aims to analyze the effect of interactive multimedia on student learning outcomes regarding the digestive system and to identify the most effective type of multimedia. This study employs a meta-analysis method using secondary data from 20 relevant scientific articles published between 2021 and 2026. Data were collected through a literature review and systematic review, then analyzed using effect size calculations with Cohen’s and Hedges’ g formulas to determine the effectiveness level of each medium. The results indicate that the use of interactive multimedia generally has a positive effect on student learning outcomes, with most media falling into the high to very high effect size category. Interactive multimedia based on Articulate Storyline was the most effective medium with the highest effect size value of 2.730, followed by Augmented Reality-based E-Magazine at 2.634. These findings indicate that interactive multimedia is effective in facilitating the visualization of concepts and increasing student engagement.